ANALISIS PENDIDIKAN KARAKTER BUKU TEKS AQIDAH AKHLAK KELAS V MADRASAH IBTIDAIYAH TAHUN 2020 - Edy Suwignyo; Moch. Hasyim Fanirin (JOEL: Journal of Educational and Language Research, 2022)
Education is the main institution that provides a major role in building a civilization. Education in Indonesia is currently facing an unfavorable situation. At least there are two main problems facing the world of education in Indonesia today. The first problem relates to the low quality of education, the second problem is a problem related to the nation's character and culture. Curriculum changes that occur in the world of education in our country certainly have their own impact, one of which is the change in textbooks used in a lesson. Likewise, in the Aqidah Akhlaq book which is used as a reference for students' handbook learning, it should be seen from the contents of the textbook to the evaluation techniques used according to the psychology of cognitive development of students. The purpose of this study was to find out how the material content and character education descriptions are in the Aqidah Akhlak textbook for class V Madrasah Ibtidaiyah. The research method is library research. The results of his research are 1. The values ​​of character education in the book Bina Aqidah and Morals of class V MI published by Erlangga in 2016 found character education values, including: (1) Religious, (2) Honest, (3) To independence, (4) Discipline, (5) Hard work, (6) Creative, (7) Independent, (8) Democratic, (9) Curiosity, (10) National spirit, (11) Love of the motherland, ( 12) Appreciate achievements, (13) Friendly and communicative, (14) Love peace, (15) Enjoy reading, (16) Care for the environment, (17) Social care, and (18) Responsibility. 2. In the book Bina Aqidah and Morals class V MI, it consists of 10 chapters/titles of material (five chapters in odd semesters and five chapters in even semesters), which are broken down into 2–4 subchapters for each chapter, so that there are a total of 33 subchapters. describes the existence of potential that leads to the development of the realm of attitudes, knowledge, and skills. Evidently, from each sub-chapter or each sub-topic, there is an In-depth Material that explains the meaning and understanding of what is mentioned or discussed in each sub-topic.